INOVASI PENGELOLAAN SAMPAH MELALUI APLIKASI E-FRASA (ELECTRONIC EFFICIENT TRASH BANK) DI DESA KRIAN, KABUPATEN SIDOARJO, JAWA TIMUR - Cantika, Marsha (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The purpose of this study is to reduce waste hoarding in Krian Village, Sidoarjo Regency, East Java. The study used quantitative methods through questionnaires for 99 respondents. This program is carried out through various stages, namely the stages of socialization, training, and practice. After socialization and training were given, the results of the study mentioned that e-Frasa (Electronic Efficient Trash Bank) is interesting management innovation, easy to implement, and in accordance with expectations. Indirectly, e-Frase is able to change people's habits to have awareness of cleanliness. In addition, the e-Frasa system also contains guidelines for the cultivation and buying, and selling of maggots bred from the organic waste collected from residents through the waste deposit system recorded on the e-Frasa. With the integrated system in e-Frasa, the author wants to facilitate citizens to be the ability to carry out waste disposal through the help of maggots, efficient recycling processes, and increase the income of citizens through maggots.